Molecular characterization of the genome-wide BOR transporter family and their responses to boron conditions in common wheat (Triticum aestivum L.) - Wang, Yuquan; Niu, Zhipeng; Hu, Xigui; Wu, Xiaojun; Yang, Zijun; Hao, Chenyan; Zhou, Mengxue; Yang, Shumin; Dong, Na; Liu, Mingjiu; Ru, Zhengang (Frontiers in Plant Science, 2022)
Boron (B) deficiency was an agricultural problem that caused significant yield losses in many countries. B transporters (BORs) were responsible for B uptake and distribution and play important roles in the formation of yields. The comprehensive analysis of BOR family members was still poorly understood in common wheat. In the present study, to clarify the molecular characterization and response to B statues, genome-wide TaBOR genes and expression patterns were investigated. Fourteen TaBOR genes were identified in common wheat by a homology search. The phylogenetic tree indicated that fourteen TaBOR genes were classified into subfamilies of TaBOR1, TaBOR3, and TaBOR4 separately. All TaBOR genes have 11-13 extrons and 10-12 introns. Most TaBOR proteins contain 10 conserved motifs and motif 1, 2, 3, 4 and 6 constituted the conserved bicarbonate (HCO3.) domain. Fourteen TaBOR genes were mapped on 13 chromosomes mainly distributed in the first, third, fifth, and seventh homologous groups. Promoters of TaBOR genes consisted of phytohormones, light responses, and stress-related cis-elements. GO analysis indicated that TaBOR genes were enriched in terms of transmembrane transport and ion homeostasis. TaBOR genes showed diverse expression profiles in different tissues. The members of TaBOR1 subfamily showed high expressions in grain, leaf, root, stem, and spike, but members of TaBOR4 subfamily were only highly expressed in spike and grain. RT-PCR indicated that TaBOR1-5A, TaBOR1-5B, and TaBOR1-5D were induced by low B and had much higher expressions in roots than shoots. TaBOR3-3A, TaBOR3-3B, TaBOR3-3D, TaBOR4-1A, TaBOR4-1B, TaBOR4-1D and TaBOR3-4B were induced by low B and high B and displayed high expressions in roots and shoots. TaBOR3-4D and TaBOR3-7B were up regulated by low B and high B, respectively, but only displayed expression in roots. Our results provided basic information on the TaBOR family, which would be helpful for dissecting the functions of TaBOR genes to overcome the problem of B deficiency.